2004
DOI: 10.1007/s00268-003-7047-z
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life after restorative proctocolectomy for ulcerative colitis: Long‐term results

Abstract: Restorative proctocolectomy (RPC) is the favorite operation for ulcerative colitis, but it may influence health-related quality of life (HRQL). Our aims were to determine the long-term HRQL of patients and its modifications after a 5-year follow-up and to identify any risk factor for a worse outcome. We enrolled 36 patients submitted to RPC (mean follow-up 8.4 +/- 4.7 years), 36 ulcerative colitis (UC) patients, and 36 healthy subjects. We used a previously validated questionnaire that explored bowel symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…Healthcare utilization should be included in future therapy studies, especially those on high-utilizing CD patients with psychiatric comorbidity and after surgical interventions. 45 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Healthcare utilization should be included in future therapy studies, especially those on high-utilizing CD patients with psychiatric comorbidity and after surgical interventions. 45 …”
Section: Discussionmentioning
confidence: 97%
“…One exclusion criterion, 279; age Ͼ 55 years, 8; refusal, 31; no acute attack within 2 years, 48; no acute attack after resection, 33; operation envisaged, 14; immunosuppressive therapy, 12; no specification, 12; ileostomy or colostomy, 6; other severe diseases, 6; wish for psychotherapy, 25; refusal of psychotherapy, 12; ongoing psychotherapy, 13; earlier psychotherapy, 14; other reasons, 45. Combination of two of these exclusion criteria, 85.…”
Section: Appendix 1: Sample Size and Randomizationmentioning
confidence: 99%
“…The differing assistance required by the patients in the two groups not only reflects on mere costs, as we demonstrated above, but also, possibly, on quality of life. In a previous paper, we demonstrated that in the long-term follow up, the quality of life of patients submitted to restorative proctocolectomy is negatively influenced by the need for medication and access to medical facilities [15]. In our opinion, the period immediately after restorative proctocolectomy, while the patient still has a temporary ileostomy, is even more delicate, and having a safe postoperative course free from any complication and with low requirement for medical care may be of crucial importance [22].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are several "minor" complications such as pressure ulcers due to the rod pressure or peristomal dermatitis that are usually managed by the stoma therapist and that virtually never or rarely arrive to the attention of the surgeon. Nevertheless, such "minor" complications need extra medical care that may significantly affect the quality of life of the patients who were submitted to a restorative proctocolectomy [14,15] and may significantly increase the management costs of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Þónokkrar rannsóknir hafa metið lífsgaeði sjúklinga sem hafa þurft að fara í ristilbrottnám vegna sáraristilbólgu. 13,14,16,19,21,[25][26][27][28][29][30][31] Mun fleiri rannsóknir fjalla um sjúklingahóp með innri garnapoka en garnarauf. Rannsókn Camilleri-Brennan á meðal sjúklinga með garnarauf sýndi fram á lífsgaeði sambaerileg og meðal almennings.…”
Section: R a N N S ó K Nunclassified